The Formulation of Vacant Residential Tax Regulation in Indonesia Based on the Principle of the Social Function of Land Rights - Tajuddin Nur‘Afas; Tunggul Anshari; M. Hamidi Masykur (Faculty of Law, Merdeka University Surabaya, Indonesia, 2027)
This study analyzes the urgency of regulating the Empty Residential Property Tax in Indonesia’s legal system based on the principle of the social function of land rights and formulates a regulatory model that can be integrated into the local tax regime. A normative juridical method is employed, using statutory, conceptual, comparative, and systematic approaches. Legal materials are analyzed qualitatively to examine the relationship between the social function of land rights, the regulatory function of taxation, and housing policy objectives. This study identifies a substantive and structural research gap. Previous studies predominantly focus on (i) the general doctrine of the social function of land rights within agrarian law, (ii) the effectiveness of Land and Building Tax in rural and urban areas (PBB-P2) as a fiscal instrument, or (iii) administrative enforcement of abandoned land regimes. However, limited attention has been given to the construction of a tax mechanism based on the actual utilization status of residential property and its normative grounding in the social function principle of land rights, particularly within Indonesia’s decentralized taxation framework. The findings indicate a normative vacuum in Indonesian positive law, where existing abandoned land mechanisms are insufficient to address intentionally vacant residential properties, while Land and Building Tax in rural and urban areas (PBB-P2) remains property-value oriented without considering occupancy status. This condition creates regulatory inefficiency, market distortion, and contributes to artificial housing scarcity, contradicting the social function principle of land rights. The novelty of this study lies in the formulation of an Empty Residential Property Tax as a progressive add-on mechanism to Land and Building Tax in rural and urban areas (PBB-P2) within the framework of the Law on Financial Relations between Central and Regional Governments. The proposed model introduces a clear vacancy threshold (more than six months per tax year), utility-based data integration as an objective verification tool, proportionate exemptions, and earmarking of revenues for affordable housing programs. This represents a shift from ownership-based taxation to utilization-based taxation in Indonesia’s property tax design.